2004
DOI: 10.1002/star.200300235
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Partial Characterization of Mexican Oxalis tuberosa Starch

Abstract: The chemical, physicochemical and rheological characteristics of Oxalis tuberosa starch were investigated. Oxalis starch presented an apparent amylose content of 33%, similar to maize starch used as control, with a granule size between 25–50 μm with oval and elliptical shapes and A‐type X‐ray diffraction pattern. The gelatinization temperature of oxalis starch was 64.0°C, that was lower than the one determined in maize starch (73.0°C), with an enthalpy value of 12.2 J/g, which was similar to that of maize star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 27 publications
5
31
0
Order By: Relevance
“…This pattern is in agreement with the enthalpy values determined, although starch from raw maize had a higher enthalpy value, this was not different of the starch isolated from the nixtamalized sample. Similar peak temperature (72.97 • C) was obtained for commercial maize starch [20]; however, lower peak temperatures (69.5 and 71.5 • C) were determined in maize starches [21,22]. Recently, in a study with starches isolated from diverse maize varieties, reported peak temperatures between 66.1 and 71.6 • C [9], that were lower than those determined in this study.…”
Section: Thermal Analysissupporting
confidence: 62%
See 1 more Smart Citation
“…This pattern is in agreement with the enthalpy values determined, although starch from raw maize had a higher enthalpy value, this was not different of the starch isolated from the nixtamalized sample. Similar peak temperature (72.97 • C) was obtained for commercial maize starch [20]; however, lower peak temperatures (69.5 and 71.5 • C) were determined in maize starches [21,22]. Recently, in a study with starches isolated from diverse maize varieties, reported peak temperatures between 66.1 and 71.6 • C [9], that were lower than those determined in this study.…”
Section: Thermal Analysissupporting
confidence: 62%
“…Recently, in a study with starches isolated from diverse maize varieties, reported peak temperatures between 66.1 and 71.6 • C [9], that were lower than those determined in this study. Respect to the gelatinization enthalpy, the value determined for starch from raw sample was similar to those reported previously (11.9-13.8 J/g) [20][21][22], but higher than those reported for different starches isolated from different maize varieties (9.3-12.6 J/g) [9]; however, the starch from nixtamalized sample showed lower enthalpy of gelatinization, as demonstrated in starches from nixtamalized pigmented maizes, where some starch granules lost their birefringence and low energy is necessary for the phase transition [23]. For raw starch the amylose-lipid complex was observed with a temper- ature of 102.1 • C and an enthalpy associated at this complex of 1.01 J/g.…”
Section: Thermal Analysismentioning
confidence: 96%
“…The samples were analyzed in a scanning electron microscope (JEOL, JSU-5600 LV, Japon and SEI, detectors, USA) operating at 15 kV accelerating voltage as reported by Sánchez [10].…”
Section: Scanning Electron Microscope (Sem)mentioning
confidence: 99%
“…Measurements were carried out during three freeze-thaw cycle. The syneresis was calculated as the ratio between the weights of the separated liquid from gel and the gel collected after centrifugation [10].…”
Section: Freeze-thaw Stability (Fts)mentioning
confidence: 99%
“…Gelatinization is required to produce the desired functionality (i.e., thickening and swelling) of starch in a food system; studies of isolated maize starch are abundant in the literature [49,71], since maize starch is widely used in various food systems as fillers or stabilizing agent. On the other hand, specialty starches have been produced to meet the needs of new product formulations; new raw materials are required to produce novel specialty starches such as starch-based fat replacers and RSs.…”
Section: Thermal Behaviormentioning
confidence: 99%